An introduction to veterinary immunology: adaptive immunity - Tizard, Ian (Henry Stewart Talks, 2020)
Characteristics of adaptive immunity, The involvement of B and T cells in adaptive immunity, Diverse types of antibodies, Immunological memory, Control of adaptive immunity, Autoimmunity and allergies in animals, Vaccines in domestic animals